INTERACTIVE VISUAL EDUCATION TO ENHANCE KNOWLEDGE OF LOW BACK PAIN AMONG THE ELDERLY AND CAREGIVERS AT OLAK KEMANG HEALTH CARE, JAMBI CITY - Humaryanto, Humaryanto; Attiya istarini; Lipinwati, Lipinwati; Perkasa, Tengku Arief Buana; Ahmad Syauqy; Hasna Dewi; Fitriyanti; Juanda, Syahreza Hadi; Zikri, Rahmat (Universitas Jambi, 2025)
Low back pain is a common degenerative illness among the elderly, significantly impacting their quality of life and independence. Insufficient understanding of effective management frequently worsens the disease. The objective of this community service program was to enhance comprehension of low back pain among elderly and their caregivers at the Olak Kemang Public Health Centre in Jambi City. The programme consisted of an instructional session with 41 participants utilising a multidisciplinary-developed interactive visual module, accompanied by a practical demonstration of stretching exercises. A pre- and post-test design was used to quantitatively evaluate the alteration in participants' knowledge. The data were examined with the Wilcoxon and Pearson chi-square tests. The findings indicated a statistically significant enhancement in participants' knowledge, with the median score increasing from 60 (range: 30-80) in the pre-test to 85 (range: 50-100) in the post-test (p < 0.001). The number of participants who attained a passing score (≥70%) rose considerably from 19 to 31 (p = 0.007). The interactive visual education program effectively enhances awareness regarding lowback pain among the elderly and their caregivers. This strategy is highly recommended for implementation in other community health programs. Keywords: Low back pain; caregiver; health education; elderly